Partial rootzone drying: effects on growth and fruit quality of field-grown grapevines (Vitis vinifera) - Santos, Tiago P. (2012)
A study to assess the effects of the Partial Rootzone Drying (PRD) irrigation strategy in comparison to other irrigation systems was carried out in southern Portugal in two field-grown grapevines varieties, Moscatel and Castelão. We addressed the question of whether by regulating growth and plant water use, the PRD system would enable an equilibrated vegetative development, leading to a favourable capture of solar radiation for photoassimilate production and, at the same time to provide an optimum environment for fruit maturation. Three irrigation schemes were applied in addition to the non-irrigated (NI) vines: partial root drying (PRD), 50% of crop evapotranspiration (ETc), supplied to only one side of the root system while the other one was allowed to dry, alternating sides every 15 days; deficit irrigated (DI), 50% ETc supplied, half to each side of the root system and full irrigated (FI, 100% ETc). During the whole season FI plants of both varieties exhibited a high leaf predawn water potential (ψpd , ca –0.2 MPa) while a progressive decline was observed in NI plants, reaching ψpd values near –0.7 MPa at the end of August. PRD and DI presented intermediate values. PRD vines exhibited a stronger control over vegetative growth as compared with DI and FI plants. This was expressed by lower values of total leaf area at harvest, leaf layer number, canopy wideness and water shoots number, allowing a higher light interception at the cluster zone that induced an improvement in some berry quality characteristics. Watering had no significant effects on sugar accumulation in the berries but led to a favourable increase in the must titratable acidity, mainly in Castelão. Whereas in DI and FI treatments berry skin anthocyanins and phenols content were always lower than in NI, in PRD there was either no reduction or the reduction was much lower than in the other irrigation treatments. Water use efficiency (WUE) was increased by about 80% in PRD and DI when compared with FI, as a result of almost similar yields in the three treatments. Yield gains of irrigated plants in relation to NI were modest, explained by the rainy spring in both years.